The Effects of Regulation on Executive Compensation - Carroll, Thomas M.; Ciscel, David H. (The Review of Economics and Statistics, 1982)
Recent economic literature has given a great deal of attention to the behavior of the firm under a regulatory constraint. Such efforts include theoretical extensions of the classic article by Averich and Johnson (1962) by Kennedy (1977), as well as empirical tests of the overcapitalization hypothesis by Leland (1974), Smithson (1978) and Spann (1974). In addition, there have been notable attempts to provide a general theory of regulation by Stigler (1971) and Peltzman (1976). Against this background, surprisingly little attention has been paid to the effect of regulation on the compensation of chief executive officers. The effect of regulation on executive rewards strikes at the heart of why regulated firms appear to behave differently than their less regulated counterparts. The only explicit attempts to relate executive compensation to the presence of regulation appear to be the work of Smyth, Boyes and Peseau (1975) and Ciscel (1977). The apparent oversight of this issue is perhaps best explained by the persistence of the controversy over the nature of the objective function of corporate decision makers introduced as the maximization' hypothesis by Baumol (1967). For the last two decades, the debate over whether corporate decision makers maximize sales or maximize profits has been couched in either-or terms. Proponents of each side of the debate, like Smyth, Boyes and Peseau (1975) and Ciscel (1974) on the managerialist side, and Lewellen and Huntsman (1970) and Masson (1971) on the neoclassical side, have produced evidence for their respective positions. Ciscel and Carroll ( 1980) provide an econometric resolution of the conflict, pointing out the compatibility of the data with both hypotheses, given a proper specification of the compensation-performance equations. Consideration of the impact of regulation on executive rewards has significance for understanding the different rewards in the regulated sectors and it illuminates the implicit incentives for executive behavior in regulated and unregulated firms. Maximum profits or optimal sales can never be directly observed. All that can be measured is whether or not the pattern of executive compensation is consistent with such maximization objectives. This aspect of economic analysis is particularly important when gauging the effect of regulation on executive pay. The impact of the absence of regulation on compensation can be contrasted to two alternatives: regulation establishes maximum prices as is the case in utilities, while regulation prescribed minimum prices as was the case in the transportation sector (see Jordan, 1972). Executive compensation reflects not only incentive changes brought about by the existence of regulation, but also the form regulation takes.